PENGARUH BIAYA PAJAK PADA PENDAPATAN ASLI DAERAH KOTA YOGYAKARTA - Krisbiantoro, RM (Prodi Magister Manajemen FE-UST, 2017)
This study was conducted to determine the effect of BPHTB and PBB P-2 towards the income generation of the Regional Income Revenue city of Yogyakarta. These results indicate that the influence BPHTB and PBB P-2 have on the income generation of the Regional Income Revenue city of Yogyakarta is not significant because of the large value of P > 0.05. These are for BPHTB against PAD is 0.977, to the PBB P-2 to PAD is 0.259, while for BPHTB and PBB P-2 simultaneously against PAD is 0.243. While the influence of Regional Regulation on BPHTB against PAD is not significant because of the P value of 0.394 and Regulation of City of Yogyakarta on the PBB P-2 does not have a significant effect on the income generation of PAD in the city of Yogyakarta as the P Value is at 0.259. From the results of test analysis coefficient of determination, (R2), is known that the test results gives a value of 0.359 to R Squere Y which means revenue of Yogyakarta is affected by BPHTB and PBB P-2 amounting to 35.9%, the remaining 64.1% is influenced by revenues from sources other Regional Income Revenues. Keywords: BPHTB, PAD, and PBB P-2, Yogyakarta